Decision Making Autonomy, Employee Involvement, and Employee Empowerment: The Mediating Role of Intrinsic Motivation in Indonesian Manufacturing Firms - Widya Fitri Lestari; Yuli Fitriyani (DPPM Universitas Pelita Bangsa, 2025)
This study presents an analysis of the effect of decision making autonomy and employee involvement in strategy planning on employee empowerment with intrinsic motivation as a mediating variable in manufacturing companies in the MM2100 area. In the era of increasingly fierce industrial competition, employee empowerment is an important strategy for companies to improve performance and competitiveness. Decision making autonomy and employee involvement in strategy planning are considered important factors that can support employee empowerment by increasing their intrinsic motivation. This research uses quantitative methods. The population used is all employees who work for manufacturing companies in the MM2100 area with a sample size of 200 respondents. The sampling used in this study is a non probability sampling technique with purposive sampling method. The data in this study were analysed using the SmartPLS version 3.0 method. The novelty of this research lies in its integration of decision making autonomy and strategic involvement as dual antecedents of empowerment within the Indonesian manufacturing context, offering a fresh perspective compared to prior studies that typically examine these constructs in isolation. Furthermore, the study contributes theoretically by extending empowerment literature to highlight the mediating role of intrinsic motivation, while also providing practical implications for managers in manufacturing firms to design participatory structures that directly enhance competitiveness.